PENGARUH KEPERCAYAAN DAN KEAMANAN TERHADAP KEPUTUSAN PENGGUNAAN E-WALLET DIKALANGAN MAHASISWA FEBI UIN STS JAMBI - Muslifatul Minanda; M. Nazori; Marissa Putriana (Nusantara Hasana Journal, 2026)
This Study Aims To Analyze The Influence Of Trust And Security On E-Wallet Usage Decisions Among Students Of The Faculty Of Islamic Economics And Business (Febi) At Uin Sts Jambi. This Research Employs A Quantitative Approach Using A Survey Method By Distributing Questionnaires To 95 Respondents Selected Through Purposive Sampling. The Data Analysis Techniques Include Validity And Reliability Tests, Classical Assumption Tests, And Multiple Linear Regression Analysis. The Results Indicate That Trust Has A Positive And Significant Effect On E-Wallet Usage Decisions, With A Significance Value Of 0.010. Security Also Has A Positive And Significant Effect On Usage Decisions, With A Significance Value Of 0.000. Simultaneously, Trust And Security Significantly Influence E-Wallet Usage Decisions, As Indicated By A Significance Value Of 0.001. The Coefficient Of Determination (Adjusted R Square) Is 0.608, Which Means That Trust And Security Variables Explain 60.8% Of The Variation In E-Wallet Usage Decisions, While The Remaining 39.2% Is Influenced By Other Variables Not Examined In This Study.These Findings Highlight That Trust And Security Are Crucial Factors In Encouraging The Adoption Of E-Wallet Services, Especially Among University Students. Therefore, E-Wallet Service Providers Need To Enhance Security Systems And Build User Trust To Ensure Sustainable Usage.